2008
DOI: 10.1590/s0100-879x2008005000026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acid-base imbalance on vascular reactivity

Abstract: Acid-base homeostasis maintains systemic arterial pH within a narrow range. Whereas the normal range of pH for clinical laboratories is 7.35-7.45, in vivo pH is maintained within a much narrower range. In clinical and experimental settings, blood pH can vary in response to respiratory or renal impairment. This altered pH promotes changes in vascular smooth muscle tone with impact on circulation and blood pressure control. Changes in pH can be divided into those occurring in the extracellular space (pH o ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 50 publications
1
37
1
3
Order By: Relevance
“…The initial changes in pH are likely offset, at least in part, by local tissue buffering at the intracellular and extracellular level (Celotto et al, 2008). However, as the hypercapnic stimulus persists and the steady-state parenchymal pCO 2 value is reached, these local homoeostatic measures are overwhelmed.…”
Section: Discussionmentioning
confidence: 99%
“…The initial changes in pH are likely offset, at least in part, by local tissue buffering at the intracellular and extracellular level (Celotto et al, 2008). However, as the hypercapnic stimulus persists and the steady-state parenchymal pCO 2 value is reached, these local homoeostatic measures are overwhelmed.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular pH regulation is mainly based on equilibrium between molecular mechanisms which cause constant inflow to and removal of H + from the cell. Removal of H + takes place through exchange with Na + and requires some energy, whereas inflow of H + is a passive process and is involved in an exchange with Cl - (Boron 2004, Balakrishnan et al 2007, Celotto et al 2008. Our own research showed that concentration of ions serving for calculation of SID and Atot in the peritoneal cavity fluid is very variable.…”
Section: Discussionmentioning
confidence: 90%
“…The mechanisms by which pH influences vascular tone or their response to specific agonists are not yet fully understood, but there is some evidence to suggest the involvement of nitric oxide (NO), prostacyclin (PGI 2 ), channels for potassium and calcium flux 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The literature presents well-designed methods to produce metabolic acidosis in vitro [3][4][5] . However, methods to induce respiratory acidosis are rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation